(untitled) (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The objective of this research work was to find out the prevalence of clinically occurring diseases and the disorders in cattle and goats at the Sylhet Agricultural University area, Sylhet during January to December 2013. Materials and methods: This clinical study was carried out on 775 clinical cases (553 cattle and 222 goats) based on the general, clinical, physical and microscopical examination along with common laboratory techniques. Results: The clinically observed cases in cattle were (i) gyneco-obstetrical (15.37%; n=85/553; P=0.038), (ii) metabolic and nutritional (9.94%; n=55/553; P=0.245), (iii) bacterial and viral (26.22%; n=145/553; P=<0.001), (iv) parasitic (26.58%; n=147/553; P=<0.001), and (v) digestive diseases (21.88%; n=121/553; P=0.008). Similarly, in goats, the prevalences were found to be 14.41 (n=32/222; P=0.041), 15.76 (n=35/222; P=0.078), 30.63 (n=68/222; P=0.001), 23.87 (n=53/222; P=0.020), and 15.31% (n=34/222; P=0.069), respectively. Conclusion: This research work is a groundwork which may facilitate the potential researchers to investigate the details possessions for extensive therapeutic exercises in Bangladesh particularly in Sylhet region for designing the control strategies and conducting the treatment of infection and disorders in cattle and goats. http://dx.doi.org/10.5455/javar.2016.c128